Karakteristik Briket Arang dengan Komposisi Serbuk Kayu Sungkai (Peronema canescens) dan Kayu Ulin (Eusideroxylon zwageri) - Wahyu Supriyati; Enti Rimma Silalahi; Nuwa Nuwa; Alpian Alpian (HUTAN TROPIKA, 2023)
Energy potential and reserves such as petroleum and natural gas available in the bowels of the earth are running low, so alternative energy is needed. Charcoal briquettes are one of the non-oil and gas energy sources that have a high enough potential to meet future needs other than oil and natural gas. Sawmills in the furniture industry produce sawdust of sungkai (Peronema canesens) and ironwood (Eusyderoxylon zwageri) wood powder which can be used as raw materials for making charcoal briquettes. The purpose of this study was to determine the quality of charcoal briquettes produced from the waste composition of sungkai sawdust and ironwood sawdust. The average test results for the physical, chemical and mechanical properties of each test treatment complied with SNI (01-62365-2000) except for density and volatile matter. The best quality of charcoal briquettes was found in treatment K1 (0% Sungkai and 100% Ulin) with density of 0.57 (g/cm3), compressive strength of 65.76 kg/cm2, moisture content of 4.08%, volatile matter content of 29 .76%, ash content 1.20%, fixed carbon content 62.77% and calorific value 6869.71 cal/g.